2015
DOI: 10.3390/su71115510
|View full text |Cite
|
Sign up to set email alerts
|

Human-Environment System Knowledge: A Correlate of Pro-Environmental Behavior

Abstract: An effective program of environmental education requires the identification of the knowledge that must be imparted. This paper compares the effects of human-environment system knowledge (i.e., knowledge related to environmental problems caused by humans) and environmental action knowledge (i.e., knowledge of possible courses of action to reduce human impact on the environment) on pro-environmental behavior. Environmental knowledge and pro-environmental behavior of 950 Chilean adults were assessed with a survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 33 publications
2
55
0
11
Order By: Relevance
“…Among multiple factors, pro-environmental behavior is related to environmental knowledge [12][13][14], connectedness to nature [15,16], and prosocial behavior [6,7,17]. It is important to note, however, that environmental education programs commonly focus on increasing students' environmental knowledge [18,19] and promoting their sense of connectedness to nature [20,21].…”
Section: Prosocial Behavior Is Not Discussed Enough In Environmental mentioning
confidence: 99%
“…Among multiple factors, pro-environmental behavior is related to environmental knowledge [12][13][14], connectedness to nature [15,16], and prosocial behavior [6,7,17]. It is important to note, however, that environmental education programs commonly focus on increasing students' environmental knowledge [18,19] and promoting their sense of connectedness to nature [20,21].…”
Section: Prosocial Behavior Is Not Discussed Enough In Environmental mentioning
confidence: 99%
“…This implies that knowledge of ecosystem functioning forms the basis for behavior related to proximal knowledge types (action and effectiveness knowledge), which, in turn, has direct effects on pro‐environmental behavior. On the contrary, Díaz‐Siefer et al (2015) found that human–environment knowledge and environmental behavior are strongly associated.…”
Section: Discussionmentioning
confidence: 92%
“…As práticas educativas devem apontar para propostas pedagógicas centradas na construção contextualizada e coletiva de conhecimento, por meio de oportunidades educacionais participativas e voltadas para mudanças de hábitos, atitudes e práticas sociais (DIAZ-SIEFER et al, 2015;BOEVE-PAUW et al, 2015 De maneira prática, são formas quase automáticas pelas quais aprendemos a realizar determinadas atividades, a partir da experiência. À medida que entendemos os hábitos cotidianos como fator importante para a compreensão da saúde da população e propulsor de mudanças ambientais (CAPON, 2014), existe a necessidade urgente de uma transição para modos de vida que respondam às necessidades de saúde das pessoas e do meio ambiente, e que estejam em sintonia com essas necessidades.…”
Section: Mudança De Hábitos Cotidianosunclassified
“…Sua prática está relacionada ao desenvolvimento econômico e ao uso de materiais que não agridam o meio ambiente, usufruindo dos recursos naturais de forma inteligente. Assim, o conceito de desenvolvimento sustentável tem sua estrutura organizada sobre quatro componentes ou dimensões: ambiental, econômica, sociopolítica e cultural (BARBOSA, 2008;DIAZ-SIEFER et al, 2015).…”
Section: Introductionunclassified
See 1 more Smart Citation